Resilient Green Energy Resources as Solution for Nigerian Energy and Environmental Crisis Through Teaching and Learning Physics - Musa, Bello; Muhammad , Bello; Musa, Lukman (Kashere Journal of Education, 2025)
This study explores resilient green energy resources as a sustainable solution to Nigeria’s dual challenges of energy insecurity and environmental pollution through the teaching and learning of Physics. The research investigates renewable energy alternatives, such as solar, wind, hydro, and biomass, analysing their resilience, efficiency, and long-term viability in the Nigerian context, as well as the role of physics education in fostering awareness, innovation, and technical capacity for renewable energy development. Data was collected from secondary sources, including reports from the Energy Commission of Nigeria and the International Renewable Energy Agency, to evaluate renewable potential, environmental impact, and economic feasibility. The findings indicate that solar and hydropower systems possess the highest resilience indexes, 0.70 and 0.79 respectively, offering strong potential for sustainable energy diversification. Moreover, renewable energy adoption could reduce national CO₂ emissions by over 60% within the next decade, aligning with Nigeria’s Energy Transition Plan and the Sustainable Development Goal on Affordable and Clean Energy. Integrating green energy concepts into physics teaching and learning is identified as a critical pathway for building skilled manpower and enhancing grassroots acceptance of clean energy technologies. The study concludes that the strategic deployment of green energy systems, supported by effective physics education, will not only stabilize power supply but also promote environmental restoration, workforce development, economic growth, and energy independence in Nigeria